Combining biochar, zeolite and wood vinegar for composting of pig manure: The effect on greenhouse gas emission and nitrogen conservation. (April 2018) - Wang, Quan; Awasthi, Mukesh Kumar; Ren, Xiuna; Zhao, Junchao; Li, Ronghua; Wang, Zhen; Wang, Meijing; Chen, Hongyu; Zhang, Zengqiang
Highlights: 10%biochar + 10%zeolite + 2.0%wood vinegar addition reduced the NH3 loss by 74.32%. 10%biochar + 10%zeolite + 2.0%wood vinegar addition decreased GHG emissions. Adding 10%biochar + 10%zeolite + 2.0%wood vinegar gave the lowest C and N loss. Abstract: The effect of enhancing wood vinegar (WV) with a mixture of biochar (B) and zeolite (Z) to compost pig manure (PM) in a 130 L reactor was evaluated to determine the levels of greenhouse gas (GHG) and ammonia emissions. Six treatments were prepared in a 2:1 ratio of PM mixed with wheat straw (WS; dry weight basis): PM + WS (control), PM + WS + 10%B, PM + WS + 10%B + 10%Z, and PM + WS with 0.5%, 1.0% and 2.0%WV combined with 10%B + 10%Z. These were composted for 50 days, and the results indicated that the combined use of B, Z, and WV could shorten the thermophilic phase and improve the maturity of compost compared to the control treatment. In addition, WV mixed with B and Z could reduce ammonia loss by 64.45–74.32% and decrease CO2, CH4, and N2 O emissions by 33.90–46.98%, 50.39–61.15%, and 79.51–81.10%, respectively. Furthermore, compared to treatments in which B and B + Z were added, adding WV was more efficient to reduce the nitrogen and carbon loss, and the 10%B + 10%Z + 2%WV treatment presented the lowest loss of carbon (9.16%) and nitrogen (0.75%). Based on the maturity indexes used, nitrogen conservation, and efficiency of GHG emissions reduction, the treatment 10%B + 10%Z + 2%WV is suggested for efficient PM composting.